Determination of benzimidazole residues and their metabolites in raw milk using high performance liquid chromatography-diode array detection - Marija Denžić Lugomer; Damir Pavliček; Nina Bilandžić; Darko Majnarić (Mljekarstvo)
A new analytical method using high performance liquid chromatography-diode array detector (HPLC-DAD) was developed for the analysis of 18 benzimidazoles and their metabolites in milk. Samples were extracted with acetonitrile and n-hexane and purified by polymer cation exchange (PCX) solid phase extraction cartridges. LC separation was performed on Xbridge C18 with gradient elution using acetonitrile and ammonium acetate buffer. The DAD detection was set at 298, 312, 254 and 290 nm. The method was validated according to the criteria of Commission Decision 2002/657/EC. The following validation parameters were set: accuracy (expressed as recovery) 31.7-137.6 %, limit of decision (CCα) 6.0-120.6 μg kg-1, detection capability (CCβ) 6.1-120.8 μg kg-1, limit of detection (LOD) 1-4 μg kg-1, limit of quantification (LOQ) 4-18 μg kg-1, precision as CV 7.0-22.5 %, withinlaboratory reproducibility expressed as CV 8.8-30.6 %. Finally, the developed method was applied to the analysis of collected milk samples. A total of 50 milk samples was analysed for benzimidazole residues. All obtained concentrations for all compounds were below the LOQ values.